Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Hasil Belajar Fisika Siswa SMA - Desti Anggistia; Eko Suyanto; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2018)
The purpose of this study is to determine the effect of problem-based learning model on physics learning outcomes of high school students from cognitive, affective, and psychomotor. The sample of this research is students of class X MIA4 and X MIA6 SMAN 14 Bandarlampung which is amount 60 students. The research design used is Posttest Control Group Design. Data from the research result is tested using normality test and Independent Sample T-test. The result of learning of cognitive aspect in experiment class got average score that is 77 higher than control class that is equal to 67, in the affective aspect of experimental class get average value that is equal to 79 higher than control class that is equal to 74, and at the psychomotor aspect of the experimental class obtained an average score of 79 higher than the control class, that is equal to 71. Based on the result of data analysis, there is a significant influence on the problem-based learning model on physics learning outcomes of high school students from the cognitive, affective, and psychomotor aspect.Tujuan penelitian ini adalah untuk mengetahui pengaruh dari model pembelajaran berbasis masalah terhadap hasil belajar fisika siswa SMA dari ranah kognitif, afektif,dan psikomotor. Sampel penelitian ini adalah siswa kelas X MIA4 dan X MIA6 SMAN 14 Bandarlampung yang berjumlah 60 siswa. Desain penelitian yang digunakan adalah Posttest Control Group Design. Data hasil uji penelitian diuji dengan analisis uji normalitas dan Independent Sample T-test. Hasil belajar ranah kognitif pada kelas eksperimen memperoleh nilai rata-rata yaitu sebesar 77 lebih tinggi dibandingkan dengan kelas kontrol yaitu sebesar 67, pada ranah afektif kelas eksperimen memperoleh nilai rata-rata yaitu sebesar 79 lebih tinggi dibandingkan dengan kelas kontrol yaitu sebesar 74, dan pada ranah psikomotor kelas eksperimen memperoleh nilai rata-rata yaitu sebesar 79 lebih tinggi dibandingkan dengan kelas kontrol yaitu 71. Berdasarkan hasil analisis data, terdapat pengaruh yang signifikan pada model pembelajaran berbasis masalah terhadap hasil belajar fisika siswa SMA dari ranah kognitif, afektif, dan psikomotor. Kata Kunci: Pembelajaran Berbasis Masalah, Hasil Belajar, Fisika.